Third Harmonic Generation Enhanced by Multipolar Interference in Complementary Silicon Metasurfaces - Chen, Shumei; Rahmani, Mohsen; Li, King Fai; Miroshnichenko, Andrey; Zentgraf, Thomas; Li, Guixin; Neshev, Dragomir; Zhang, Shuang (ACS Photonics)

Spin and Geometric Phase Control Four-Wave Mixing from Metasurfaces - Li, Guixin; Sartorello, Giovanni; Chen, Shumei; Nicholls, Luke H.; Li, King Fai; Zentgraf, Thomas; Zhang, Shuang; Zayats, Anatoly V. (Laser & Photonics Reviews)

Coresets for Fuzzy K-Means with Applications - Blömer, Johannes; Brauer, Sascha; Bujna, Kathrin (29th International Symposium on Algorithms and Computation (ISAAC 2018))

Analysing Constructional Change: Linguistic Annotation and Sources of Uncertainty - Merten, Marie-Luis; Seemann, Nina (Proceedings of the 6th International Conference on Technological Ecosystems for Enhancing Multiculturality (TEEM'18))
This paper presents the various sources of uncertainty we encounter in our project. Our research focus lies on the investigation of language elaboration processes in Middle Low German. We are particularly interested in diachronic constructional changes and constructionalizations involving and affecting all linguistic dimensions. For this, it is necessary to annotate our corpus with Part-of-Speech and constructional tags. Here, we are confronted with gradualness, gradience, and ambiguity as potential sources of uncertainty that complicate the annotation process. Furthermore, due to the historicity of the investigated language, we expect cases of incomplete knowledge and comparative fallacy from the annotators. For this reason, we develop an interface that captures all annotators’ doubts.
Keywords: historical languages; linguistic annotations; gradience and gradualness; ambiguity; incomplete knowledge

Towards a Multi-Stage Approach to Detect Privacy Breaches in Physician Reviews - Bäumer, Frederik Simon; Kersting, Joschka; Orlikowski, Matthias; Geierhos, Michaela (Proceedings of the Posters and Demos Track of the 14th International Conference on Semantic Systems co-located with the 14th International Conference on Semantic Systems (SEMANTiCS 2018))
Physician Review Websites allow users to evaluate their experiences with health services. As these evaluations are regularly contextualized with facts from users’ private lives, they often accidentally disclose personal information on the Web. This poses a serious threat to users’ privacy. In this paper, we report on early work in progress on “Text Broom”, a tool to detect privacy breaches in user-generated texts. For this purpose, we conceptualize a pipeline which combines methods of Natural Language Processing such as Named Entity Recognition, linguistic patterns and domain-specific Machine Learning approaches which have the potential to recognize privacy violations with wide coverage. A prototypical web application is openly accesible.
Keywords: Detection of Privacy Violations; Physician Reviews

Nonpolar Cubic III-nitrides: From the Basics of Growth to Device Applications - As, Donat Josef; Lischka, Klaus (Molecular Beam Epitaxy)

Self-stabilizing Overlays for high-dimensional Monotonic Searchability - Feldmann, Michael; Kolb, Christina; Scheideler, Christian (Proceedings of the 20th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
We extend the concept of monotonic searchability~\cite{DBLP:conf/opodis/ScheidelerSS15}~\cite{DBLP:conf/wdag/ScheidelerSS16} for self-stabilizing systems from one to multiple dimensions. A system is self-stabilizing if it can recover to a legitimate state from any initial illegal state. These kind of systems are most often used in distributed applications. Monotonic searchability provides guarantees when searching for nodes while the recovery process is going on. More precisely, if a search request started at some node $u$ succeeds in reaching its destination $v$, then all future search requests from $u$ to $v$ succeed as well. Although there already exists a self-stabilizing protocol for a two-dimensional topology~\cite{DBLP:journals/tcs/JacobRSS12} and an universal approach for monotonic searchability~\cite{DBLP:conf/wdag/ScheidelerSS16}, it is not clear how both of these concepts fit together effectively. The latter concept even comes with some restrictive assumptions on messages, which is not the case for our protocol. We propose a simple novel protocol for a self-stabilizing two-dimensional quadtree that satisfies monotonic searchability. Our protocol can easily be extended to higher dimensions and offers routing in $\mathcal O(\log n)$ hops for any search request.

Editorial for the theories and applications of metasurfaces - Guo, Zhongyi; Chen, Xianzhong; Zentgraf, Thomas (Journal of Physics D: Applied Physics)

Controlling the phase of optical nonlinearity with plasmonic metasurfaces - Chen, Shumei; Li, Guixin; Cheah, Kok Wai; Zentgraf, Thomas; Zhang, Shuang (Nanophotonics)

Nanoscale Polarization Manipulation and Encryption Based on Dielectric Metasurfaces - Zhao, Ruizhe; Huang, Lingling; Tang, Chengchun; Li, Junjie; Li, Xiaowei; Wang, Yongtian; Zentgraf, Thomas (Advanced Optical Materials)

What Drives Paid Search Success: A Systematic Literature Review - Schlangenotto, Darius; Kundisch, Dennis; Poniatowski, Martin (Proceedings of the 24th Americas Conference on Information Systems (AMCIS))

An Extended Perspective of Technology Pivots in Software Startups: Towards a Theoretical Model - Bohn, Nicolai; Kundisch, Dennis (Proceedings of the 39th International Conference on Information Systems (ICIS))

The Economics of Online Reviews in Markets with Variety-Seeking Consumers - Neumann, Jürgen (INFORMS Conference on Information Systems and Technology (CIST))

Towards software-based tools for business model development: Using external stimuli for business model idea generation - Szopinski, Daniel (Bosch Business Model Innovation Summit 2018)

A Peer-to-Peer based Cloud Storage supporting orthogonal Range Queries of arbitrary Dimension - Benter, Markus; Knollmann, Till; Meyer auf der Heide, Friedhelm; Setzer, Alexander; Sundermeier, Jannik (Proceedings of the 4th International Symposium on Algorithmic Aspects of Cloud Computing (ALGOCLOUD))
We present a peer-to-peer network that supports the efficient processing of orthogonal range queries $R=\bigtimes_{i=1}^{d}[a_i,\,b_i]$ in a $d$-dimensional point space.\\ The network is the same for each dimension, namely a distance halving network like the one introduced by Naor and Wieder (ACM TALG'07). We show how to execute such range queries using $\mathcal{O}\left(2^{d'}d\,\log m + d\,|R|\right)$ hops (and the same number of messages) in total. Here $[m]^d$ is the ground set, $|R|$ is the size and $d'$ the dimension of the queried range. Furthermore, if the peers form a distributed network, the query can be answered in $\mathcal{O}\left(d\,\log m + d\,\sum_{i=1}^{d}(b_i-a_i+1)\right)$ communication rounds. Our algorithms are based on a mapping of the Hilbert Curve through $[m]^d$ to the peers.
Keywords: Distributed Storage; Multi-Dimensional Range Queries; Peer-to-Peer; Hilbert Curve

Implikationen der US-Steuerreform auf die Hinzurechnungsbesteuerung nach dem AStG - Schümmer, Markus; Leusder, Johannes; Weinrich, Arndt (IStR Internationales Steuerrecht)
1. Effektive Besteuerung von Outbound-Investitionen in den USA 2. Qualifikation von Einkünften als passiv 3. Anwendung des Motivtests auf die USA? 4. Fazit und Ausblick
Keywords: Effektive Besteuerung von Outbound-Investitionen in den USA Qualifikation von Einkünften als passiv Anwendung des Motivtests auf die USA

Flexible Ambiguity Resolution and Incompleteness Detection in Requirements Descriptions via an Indicator-based Configuration of Text Analysis Pipelines - Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 51st Hawaii International Conference on System Sciences)
Natural language software requirements descriptions enable end users to formulate their wishes and expectations for a future software product without much prior knowledge in requirements engineering. However, these descriptions are susceptible to linguistic inaccuracies such as ambiguities and incompleteness that can harm the development process. There is a number of software solutions that can detect deficits in requirements descriptions and partially solve them, but they are often hard to use and not suitable for end users. For this reason, we develop a software system that helps end-users to create unambiguous and complete requirements descriptions by combining existing expert tools and controlling them using automatic compensation strategies. In order to recognize the necessity of individual compensation methods in the descriptions, we have developed linguistic indicators, which we present in this paper. Based on these indicators, the whole text analysis pipeline is ad-hoc configured and thus adapted to the individual circumstances of a requirements description.
Keywords: Software Product Lines: Engineering; Services; and Management; Ambiguities; Incompleteness; Natural Language Processing; Software Requirements

Do Android taint analysis tools keep their promises? - Pauck, Felix; Bodden, Eric; Wehrheim, Heike (Proceedings of the 2018 26th ACM Joint Meeting on European Software Engineering Conference and Symposium on the Foundations of Software Engineering - ESEC/FSE 2018)

I thought it was over, but now it is back: customer reactions to ex post time extensions of sales promotions - Garnefeld, Ina; Boehm, Eva; Klimke, Lena; Oestreich, Andrea (Journal of the Academy of Marketing Science)

Tax Avoidance and Accounting Conservatism - Bornemann, Tobias
This study analyzes the relation between accounting conservatism, future tax rate cuts and countries’ level of book-tax conformity. Firms have an incentive to increase conservatism in ﬁnancial reporting when a tax rate cut is imminent to shift taxable income into the lower taxed future. Using a panel of ﬁrms across 18 countries from 1995 to 2010 I ﬁnd that conditional conservatism is positively and signiﬁcantly associated with future tax rate cuts when book-tax conformity is high. This eﬀect is particularly pronounced for ﬁrms that concentrate the majority of their operations in the country in which the tax rate is cut. In contrast, there is no signiﬁcant relation between future tax rate cuts and unconditional conservatism.

Do Transfer Pricing Rules Distort R&D Investment Decisions? - Bornemann, Tobias
This study analyzes the impact of transfer pricing on multinational enterprises’ R&D investment decisions. Speciﬁcally, I examine the eﬀects of two commonly used contract designs to exchange and develop intangible assets across group aﬃliates: licensing and cost sharing agreements. Whilst serving as a tool to allocate taxable income between group aﬃliates, the economic implications of licensing and cost sharing agreements diﬀer. Whereas licensing agreements provide for a sharing rule on the intangible’s proﬁts, cost sharing agreements on the other hand provide a sharing rule on R&D development costs. This diﬀerence matters when ﬁrms simultaneously use internal transfer prices to allocate taxable income and provide local management with suﬃcient investment incentives. Using a multiple-agent, moral hazard investment framework I model a multinational ﬁrm with comparable group afﬁliates in two countries that delegates the R&D investment decision to a local risk and eﬀort averse aﬃliate manager. The results suggest that the optimal contract not only depends on available tax beneﬁts, but also on R&D investment and manager speciﬁc characteristics. A licensing agreement provides management with larger incentives to invest in R&D mitigating agency concerns associated with R&D. On the other hand, using a cost sharing agreement the ﬁrm can cater diﬀerent risk preferences among managers potentially increasing investment. The arm’s length principle however may distort an eﬃcient allocation of R&D costs when using a cost sharing agreement.

Taxation and Agency Conflicts between Firm Owners and Managers: A Review - Bauer, Thomas; Kourouxous, Thomas; Krenn, Peter (Business Research)
When analyzing the influence of taxation on agency conflicts between firm owners and managers, one can draw on theoretical principal–agent literature from various research fields. In recent years, this interdisciplinary research has grown significantly covering research with regards to optimal compensation, investment decisions, tax avoidance and transfer pricing while analyzing the effects of corporate income taxes, wage taxes, bonus taxes and shareholder taxes. Our paper provides a comprehensive review of analytical literature that studies the influence of taxation on agency conflicts between firm owners and managers. Above and beyond summarizing research findings, we discuss how taxes are commonly implemented in agency models, derive empirical predictions, and identify research gaps for future tax research.

Digitale Transformation von Dienstleistungssystemen - Beverungen, Daniel; Wolf, Verena; Bartelheimer, Christian (Service Business Development)

Product market effects of IFRS adoption - Downes, Jimmy F; Flagmeier, Vanessa; Godsell, David (Journal of Accounting and Public Policy)
Prior literature finds that International Financial Reporting Standards (IFRS) adopters enjoy lower financing costs subsequent to IFRS adoption. We predict and find that mandatory IFRS adopters exploit lower financing costs to increase market share vis-à-vis non-adopters. This effect is robust across several different model specifications in a sample capturing the universe of public and private firms in the EU, in a matched sample of public and private firms, and in a public firm sample comparing mandatory and voluntary IFRS adopters. We further find that IFRS is associated with an increase (decrease) in industry sales concentration (competition), consistent with large public firms increasing market share. In supplemental analyses, we find that mandatory adopters issue more equity and debt after IFRS adoption and that larger market share gains accrue to those mandatory IFRS adopters that issue more equity and debt after IFRS adoption. Overall, we provide evidence of unintended product market consequences of IFRS adoption.
Keywords: Financial reporting regulationProduct market competition

Mandatory CSR reporting—literature review and future developments in Germany - Gulenko, Maryna (NachhaltigkeitsManagementForum| Sustainability Management Forum)

Demografiegerechtes Verbraucherrecht? – Die Verbraucherstellung im Spiegel sozialer, wirtschaftlicher und technologischer Prozesse - Müller, Stefan; Kluge, Vanessa (Jenseits des Otto Normalverbrauchers – Verbraucherpolitik in Zeiten des „unmanageable consumer“)
Während das Verbraucherprivatrecht an sich recht dicht reguliert ist, hat es demografische Entwicklungen und Kenngrößen bislang noch nicht gezielt aufgegriffen. Doch altersbedingte Einschränkungen oder Sprach- und Technikbarrieren können die praktische Wirksamkeit des Verbraucherrechts in "demografisch geprägten" Sachverhalten in Frage stellen. Der vorliegende Beitrag möchte den Stand des Verbraucherrechts daraufhin untersuchen, ob das Recht demografieblind ist oder ob Anknüpfungspunkte bestehen, welche die Aufnahme individueller Alters-, Migrations- und Kulturerfahrungen bei der Ausformung des Verbraucherrechts gestatten....

As Prices Peak, Should Dealmakers wait for the next Downturn? - Sievers, Sönke; Kengelbach, Jens; Keienburg, Georg; Schmid, Timo; Degen, Dominik (The Boston Consulting Group, Inc.)

CrySL: An Extensible Approach to Validating the Correct Usage of Cryptographic APIs - Krüger, Stefan; Späth, Johannes; Ali, Karim; Bodden, Eric; Mezini, Mira (European Conference on Object-Oriented Programming (ECOOP))
Keywords: ITSECWEBSITE; CROSSING

Relays: A New Approach for the Finite Departure Problem in Overlay Networks - Scheideler, Christian; Setzer, Alexander (Proceedings of the 20th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS 2018))
A fundamental problem for overlay networks is to safely exclude leaving nodes, i.e., the nodes requesting to leave the overlay network are excluded from it without affecting its connectivity. To rigorously study self-stabilizing solutions to this problem, the Finite Departure Problem (FDP) has been proposed [9]. In the FDP we are given a network of processes in an arbitrary state, and the goal is to eventually arrive at (and stay in) a state in which all leaving processes irrevocably decided to leave the system while for all weakly-connected components in the initial overlay network, all staying processes in that component will still form a weakly connected component. In the standard interconnection model, the FDP is known to be unsolvable by local control protocols, so oracles have been investigated that allow the problem to be solved [9]. To avoid the use of oracles, we introduce a new interconnection model based on relays. Despite the relay model appearing to be rather restrictive, we show that it is universal, i.e., it is possible to transform any weakly-connected topology into any other weakly-connected topology, which is important for being a useful interconnection model for overlay networks. Apart from this, our model allows processes to grant and revoke access rights, which is why we believe it to be of interest beyond the scope of this paper. We show how to implement the relay layer in a self-stabilizing way and identify properties protocols need to satisfy so that the relay layer can recover while serving protocol requests.

On Underlay-Aware Self-Stabilizing Overlay Networks - Götte, Thorsten; Scheideler, Christian; Setzer, Alexander (Proceedings of the 20th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS 2018))
We present a self-stabilizing protocol for an overlay network that constructs the Minimum Spanning Tree (MST) for an underlay that is modeled by a weighted tree. The weight of an overlay edge between two nodes is the weighted length of their shortest path in the tree. We rigorously prove that our protocol works correctly under asynchronous and non-FIFO message delivery. Further, the protocol stabilizes after O(N^2) asynchronous rounds where N is the number of nodes in the overlay.

Maintaining vs. Milking Good Reputation when Customer Feedback is Inaccurate - Mir Djawadi, Behnud; Fahr, Rene; Haake, Claus-Jochen; Recker, Sonja (PLoS ONE)
In Internet transactions, customers and service providers often interact once and anonymously. To prevent deceptive behavior a reputation system is particularly important to reduce information asymmetries about the quality of the offered product or service. In this study we examine the effectiveness of a reputation system to reduce information asymmetries when customers may make mistakes in judging the provided service quality. In our model, a service provider makes strategic quality choices and short-lived customers are asked to evaluate the observed quality by providing ratings to a reputation system. The customer is not able to always evaluate the service quality correctly and possibly submits an erroneous rating according to a predefined probability. Considering reputation profiles of the last three sales, within the theoretical model we derive that the service provider’s dichotomous quality decisions are independent of the reputation profile and depend only on the probabilities of receiving positive and negative ratings when providing low or high quality. Thus, a service provider optimally either maintains a good reputation or completely refrains from any reputation building process. However, when mapping our theoretical model to an experimental design we find that a significant share of subjects in the role of the service provider deviates from optimal behavior and chooses actions which are conditional on the current reputation profile. With respect to these individual quality choices we see that subjects use milking strategies which means that they exploit a good reputation. In particular, if the sales price is high, low quality is delivered until the price drops below a certain threshold, and then high quality is chosen until the price increases again.

Monotone Suchbarkeit bei den selbststabilisierenden Protokollen Build-List und Build-Multilist mit systemverlassenden Knoten - Jochmaring, Moritz

Mobile Facility Leasing - Geromel, Marcel

Online Algorithmen für das k-Page Migration Problem - Kolpaczki, Patrick Irenäus

Study Effects of Approximation on Conjugate Gradient Algorithm and Accelerate it on FPGA Platform - Filmwala, Tasneem

Programmable Programs? - Designing FPGA Overlay Architectures with OpenCL - Gadewar, Onkar

Vertrauen und Vertrauenswürdigkeit - Akteure auf Cloud-basierten Plattformen - Diemke, Viktoria

Implementierung und Analyse von Searchable Encryption - von Heißen, Oliver

The more the merrier? Immigrant share and entrepreneurial activities. - Li, C; Dau, L A; Kabst, Rüdiger (Entrepreneurship Theory and Practice.)

Embracing the foreign: Cultural attractiveness and international strategy. - Li, C; Brodbeck, F C; Shenkar, O; Ponzi, L J; Fischer, J (Strategic Management Journal.)

Practical and Tightly-Secure Digital Signatures and Authenticated Key Exchange - Gjøsteen, Kristian; Jager, Tibor (Advances in Cryptology - CRYPTO 2018 - 38th Annual International Cryptology Conference, Santa Barbara, CA, USA, August 19-23, 2018, Proceedings, Part II)

Age Diversity and team outcomes: A quantitative review. - Schneid, M; Isidor, R; Steinmetz, Holger; Kabst, Rüdiger (Journal of Managerial Psychology.)

The Impact of Structural and Attitudinal Antecedents on the Instability of International Joint Ventures: The Mediating Role of Asymmetrical Changes in Commitment. - Isidor, R; Schwens, C; Hornung, F; Kabst, Rüdiger (International Business Review (IBR).)

On the Security of the PKCS#1 v1.5 Signature Scheme - Jager, Tibor; Kakvi, Saqib; May, Alexander (Proceedings of the 2018 ACM SIGSAC Conference on Computer and Communications Security - CCS '18)

Different Stages of Entrepreneurship: Lessons From the Transtheoretical Model of Change. - Klonek, F; Isidor, R; Kauffeld, S (Journal of Change Management.)

Der Einfluss bio-demographischer und fachlicher Diversität auf die Leistung von Teams: Eine Metaanalyse. - Schneid, M; Isidor, R; Schwens, C; Kabst, Rüdiger; Weber, I (Die Betriebswirtschaft.)

Simulation leitungsgeführter Störspannungen von DC-DC-Wandlern - Baumgarten, Tim; Scholz, Peter; Sievers, Denis; Förstner, Jens (Elektromagnetische Verträglichkeit - Internationale Fachmesse und Kongress 2018)
In diesem Beitrag werden simulatorische und messtechnische EMV-Untersuchungen von Gleichspannungswandlern vorgestellt. Der Fokus liegt auf leitungsgeführten Störspannungen, ihre Abhängigkeit vom Schaltungslayout und ihre Unterdrückung durch Filterung. Der Simulationsprozess besteht aus kombinierten Feld- und Netzwerksimulationen. Zur Bewertung der Simulationsresultate werden zwei Prototypen gezeigt, die gute und schlechte EMV-Eigenschaften aufweisen. Bei der Beurteilung der Resultate wird insbesondere Wert auf die Untersuchung gelegt, inwieweit einfache Schaltungssimulationen ausreichen, um leitungsgeführte Störspannungen korrekt vorherzusagen und wann aufwändigere Feldsimulationen notwendig sind.

Engaging a product-oriented salesforce in solution sales - Salonen, A; Terho, H; Boehm, E; Rajala, R; Virtanen, A

How to transform a product-focused salesforce to solution sales? - Salonen, A; Terho, H; Boehm, E; Rajala, R; Virtanen, A

Patterns of Store-oriented Software Ecosystems: Detection, Classification, and Analysis of Design Options - Jazayeri, Bahar; Zimmermann, Olaf; Küster, Jochen; Engels, Gregor; Kundisch, Dennis; Szopinski, Daniel (The Latin American Conference on Pattern Languages of Programs (SLPLoP))
Software companies nowadays create ecosystems of users and third-party providers around their platforms. They often provide online stores so that the third-party developments can be exposed to users directly. The resulting ecosystems differ significantly from each other in their architectural designs because their providers differ in terms of business goals and contexts. Until now, this architectural diversity and rationale behind it are not well-understood. Therefore, it is not clear which software features contribute to ecosystem’s success with respect to certain business goals and context. This hinders systematic creation of ecosystems in the future. Thus, decision-making becomes too risky; for future ecosystem providers, which may lead to creation of inefficient ecosystems that lack critical features, and for third-party providers to rely on ad-hoc choices while deciding on suitability of an ecosystem for their future career. In this paper, we introduce three design patterns for store- oriented software ecosystems by classifying the design decisions, business goals, and context of 111 store-oriented software ecosystems. Each design pattern provides an architectural solution to achieve a different business goal while supporting a different context. We discuss how the design patterns are applied together in order to achieve more business goals. Our work supports ecosystem and third-party providers by sharing practice-proven architectural solutions, helping them to take informed architectural decisions and reduce technical risks.

Business Intelligence and Analytics Cost Accounting: An Empirical Study of the Perceptions of Stakeholders and Their Implications - Grytz, Raphael; Krohn-Grimberghe, Artus (International Journal of Systems and Service-Oriented Engineering)

A Highly Accurate Energy Model for Task Execution on Heterogeneous Compute Nodes - Lösch, Achim; Platzner, Marco (2018 IEEE 29th International Conference on Application-specific Systems, Architectures and Processors (ASAP))

Information Security Investments: An Exploratory Multiple Case Study on Decision-Making, Evaluation and Learning - Weishäupl, Eva; Yasasin, Emrah; Schryen, Guido (Computers & Security)
The need to protect resources against attackers is reflected by huge information security investments of firms worldwide. In the presence of budget constraints and a diverse set of assets to protect, organizations have to decide in which IT security measures to invest, how to evaluate those investment decisions, and how to learn from past decisions to optimize future security investment actions. While the academic literature has provided valuable insights into these issues, there is a lack of empirical contributions. To address this lack, we conduct a theory-based exploratory multiple case study. Our case study reveals that (1) firms? investments in information security are largely driven by external environmental and industry-related factors, (2) firms do not implement standardized decision processes, (3) the security process is perceived to impact the business process in a disturbing way, (4) both the implementation of evaluation processes and the application of metrics are hardly existent and (5) learning activities mainly occur at an ad-hoc basis.
Keywords: Information Security Investments; Multiple Case Study; Organizations; Single Loop Learning; Double Loop Learning

Information Systems Design Science Research and Cumulative Knowledge Development: An Exploratory Study - Schuster, Richard; Wagner, Gerit; Schryen, Guido (Proceedings of the 2018 International Conference on Information Systems (ICIS 2018))

A Prototyping Platform to Validate and Verify Network Service Header-based Service Chains - Peuster, Manuel; Schneider, Stefan Balthasar; Christ, Frederic; Karl, Holger (IEEE Conference on Network Function Virtualisation and Software Defined Networks (NFV-SDN) 5GNetApp)

Methodology for VNF Benchmarking Automation - Rosa, Raphael Vicente; Rothenberg, Christian Esteve; Peuster, Manuel; Karl, Holger

Theory of spin inertia in singly charged quantum dots - Smirnov, D. S.; Zhukov, E. A.; Kirstein, E.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Greilich, A.; Glazov, M. M. (Physical Review B)

Sprint diagnostic with GPS and inertial sensor fusion - Mertens, Jan Cedric; Boschmann, Alexander; Schmidt, M.; Plessl, Christian (Sports Engineering)

Simple and effective methods to match photovoltaic power generation to the grid load profile for a PV based energy system. - Krauter, Stefan (Solar Energy)

An inverse approach to the characterisation of material parameters of piezoelectric discs with triple-ring-electrodes - Feldmann, Nadine; Jurgelucks, Benjamin; Claes, Leander; Schulze, Veronika; Henning, Bernd; Walther, Andrea (tm - Technisches Messen)

An acoustic waveguide-based approach to the complete characterisation of linear elastic, orthotropic material behaviour - Johannesmann, Sarah; Düchting, Julia; Webersen, Manuel; Claes, Leander; Henning, Bernd (tm - Technisches Messen)
Keywords: Continous-fibre reinforced plastics; material parameters; orthotropy; ultrasonics

Acoustic material characterization of prestressed, plate-shaped specimens - Johannesmann, Sarah; Brockschmidt, Tobias; Rump, Friedhelm; Webersen, Manuel; Claes, Leander; Henning, Bernd (Sensoren und Messsysteme)

Guided ultrasonic waves for determining effective orthotropic material parameters of continuous-fiber reinforced thermoplastic plates - Webersen, Manuel; Johannesmann, Sarah; Düchting, Julia; Claes, Leander; Henning, Bernd (Ultrasonics)

Akustische Charakterisierung der richtungsabhängigen elastischen Eigenschaften faserverstärkter Kunststoffe - Webersen, Manuel; Johannesmann, Sarah; Düchting, Julia; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2018)

Efficient optimisation of initial values for characterising piezoelectric material parameters - Feldmann, Nadine; Henning, Bernd (Fortschritte der Akustik)

Extraction of Interpretable Features from Temporal Measurements using Approximate Prototypes - Thiel, Christian; Feldmann, Nadine; Henning, Bernd (Sensoren und Messsysteme 2018)

Materialparameter von bleihaltigen und bleifreien Piezokeramiken und ihre Bedeutung in der Anwendung - Claes, Leander; Feldmann, Nadine; Henning, Bernd

Additiv gefertigte, akustische Diffusor-Strukturen für Ultraschallanwendungen - Claes, Leander; Zeipert, Henning; Koppa, Peter; Tröster, Thomas; Henning, Bernd

Vollständige Charakterisierung von piezoelektrischen Scheiben mit Ringelektroden - Feldmann, Nadine; Jurgelucks, Benjamin; Claes, Leander; Henning, Bernd

Einfluss mechanischer Vorspannung auf das mechanische Materialverhalten von Polymeren - Webersen, Manuel; Johannesmann, Sarah; Brockschmidt, Tobias; Rump, Friedhelm; Claes, Leander; Henning, Bernd

Models and Constructions for Secure Reputation Systems - Juhnke, Jakob

Congestion games with mixed objectives - Feldotto, Matthias; Leder, Lennart; Skopalik, Alexander (Journal of Combinatorial Optimization)
We study a new class of games which generalizes congestion games andits bottleneck variant. We introduce congestion games with mixed objectives to modelnetwork scenarios in which players seek to optimize for latency and bandwidths alike.We characterize the (non-)existence of pure Nash equilibria (PNE), the convergenceof improvement dynamics, the quality of equilibria and show the complexity of thedecision problem. For games that do not possess PNE we give bounds on the approx-imation ratio of approximate pure Nash equilibria.

Individual and Social Influences on Professional Learning - Gruber, Hans; Harteis, Christian

Einsatz von Classroom-Response-Systemen und Peer Instruction in der Veranstaltung Grundlagen von Datenbanken - Wolters, Dennis (die hochschullehre)

Context-specific Quality Evaluation of Test Cases - Jovanovikj, Ivan; Narasimhan, Vishwak; Engels, Gregor; Sauer, Stefan (Proceedings of the 6th International Conference on Model-Driven Engineering and Software Development - Volume 1: MODELSWARD,)

Model-Driven Test Case Migration: The Test Case Reengineering Horseshoe Model - Jovanovikj, Ivan; Engels, Gregor; Anjorin, Anthony; Sauer, Stefan (Information Systems in the Big Data Era - CAiSE Forum 2018, Tallinn, Estonia, June 11-15, 2018, ProceedingIs)
Existing test cases represent important assets, which are worth reusing in software migration projects. The benefit is twofold, reuse of relevant information as well cost saving by avoiding design of new test cases. As test cases are implemented in the same or a compatible technology as the system they are testing, they have to somehow follow the system migration, i.e., they should be co-migrated. Due to the size of the test case set, and often missing conformity in the structure of the test cases, migration of test cases is a quite challenging task. As model-driven engineering has been established to manage those complex tasks, we apply it in the test case domain. In this paper, we propose a generic migration method based on model-driven reengineering techniques. Our method which involves reverse engineering, restructuring, and forward engineering is applied in an industrial case study where appropriate tooling was developed as well.

Mechanized proofs of opacity: a comparison of two techniques - Derrick, John; Doherty, Simon; Dongol, Brijesh; Schellhorn, Gerhard; Travkin, Oleg; Wehrheim, Heike (Formal Asp. Comput.)

Making Linearizability Compositional for Partially Ordered Executions - Doherty, Simon; Dongol, Brijesh; Wehrheim, Heike; Derrick, John (Integrated Formal Methods - 14th International Conference, IFM 2018, Maynooth, Ireland, September 5-7, 2018, Proceedings)

Making Linearizability Compositional for Partially Ordered Executions - Doherty, Simon; Dongol, Brijesh; Wehrheim, Heike; Derrick, John (Integrated Formal Methods - 14th International Conference, IFM 2018, Maynooth, Ireland, September 5-7, 2018, Proceedings)

Brief Announcement: Generalising Concurrent Correctness to Weak Memory - Doherty, Simon; Dongol, Brijesh; Wehrheim, Heike; Derrick, John (32nd International Symposium on Distributed Computing, DISC 2018, New Orleans, LA, USA, October 15-19, 2018)

Model-integrating development of software systems: a flexible component-based approach - Derakhshanmanesh, Mahdi; Ebert, Jürgen; Grieger, Marvin; Engels, Gregor (Software & Systems Modeling)

Trade-offs in Dynamic Resource Allocation in Network Function Virtualization - Schneider, Stefan Balthasar; Dräxler, Sevil; Karl, Holger (IEEE Global Communications Conference (GLOBECOM 2018))
Dynamic allocation of resources is a key feature in network function virtualization (NFV), enabling flexible adjustment of slices and contained network services to ever-changing service demands. Considering resource allocation across the entire network, many authors have proposed approaches to optimize the placement and chaining of virtual network function (VNF) instances and the allocation of resources to these VNF instances. In doing so, various optimization objectives are conceivable, e.g., minimizing certain required resources or the end-to-end delay of the placed services. In this paper, we investigate the relationship between four typical optimization objectives when coordinating the placement and resource allocation of chained VNF instances. We observe an interesting trade-off between minimizing the overhead of starting/stopping VNF instances and all other objectives when adapting to changed service demands.

A Generic Emulation Framework for Reusing and Evaluating VNF Placement Algorithms - Schneider, Stefan Balthasar; Peuster, Manuel; Karl, Holger (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN 2018))
In recent years, a variety of different approaches have been proposed to tackle the problem of scaling and placing network services, consisting of interconnected virtual network functions (VNFs). This paper presents a placement abstraction layer (PAL) that provides a clear and simple northbound interface for using such algorithms while hiding their internal functionality and implementation. Through its southbound interface, PAL can connect to different back ends that evaluate the calculated placements, e.g., using simulations, emulations, or testbed approaches. As an example for such evaluation back ends, we introduce a novel placement emulation framework (PEF) that allows executing calculated placements using real, containerbased VNFs on real-world network topologies. In a case study, we show how PAL and PEF facilitate reusing and evaluating placement algorithms as well as validating their underlying models and performance claims.

A Fully Integrated Multi-Platform NFV SDK - Schneider, Stefan Balthasar; Peuster, Manuel; Tavernier, Wouter; Karl, Holger (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN 2018))
A key challenge of network function virtualization (NFV) is the complexity of developing and deploying new network services. Currently, development requires many manual steps that are time-consuming and error-prone (e.g., for creating service descriptors). Furthermore, existing management and orchestration (MANO) platforms only offer limited support of standardized descriptor models or package formats, limiting the re-usability of network services. To this end, we introduce a fully integrated, open-source NFV service development kit (SDK) with multi-MANO platform support. Our SDK simplifies many NFV service development steps by offering initial generation of descriptors, advanced project management, as well as fully automated packaging and submission for on-boarding. To achieve multi-platform support, we present a package format that extends ETSI’s VNF package format. In this demonstration, we present the end-to-end workflow to develop an NFV service that is then packaged for multiple platforms, i.e., 5GTANGO and OSM.

Breaking the Synchronization Bottleneck with Reconfigurable Transactional Execution - Li, Zhaoshi; Liu, Leibo; Deng, Yangdong; Yin, Shouyi; Wei, Shaojun (IEEE Computer Architecture Letters)
The advent of FPGA-based hybrid architecture offers the opportunity of customizing memory subsystems to enhance the overall system performance. However, it is not straightforward to design efficient FPGA circuits for emerging FPGAs applications such as in-memory database and graph analytics, which heavily depend on concurrent data structures (CDS'). Highly dynamic behaviors of CDS' have to be orchestrated by synchronization primitives for correct execution. These primitives induce overwhelming memory traffic for synchronizations on FPGAs. This paper proposes a novel method for systematically exploring and exploiting memory-level parallelism (MLP) of CDS by transactional execution on FPGAs. Inspired by the idea that semantics of transactions can be implemented in a more efficient and scalable manner on FPGAs than on CPUs, we propose a transaction-based reconfigurable runtime system for capturing MLP of CDS'. Experiments on linked-list and skip-list show our approach achieves 5.18x and 1.55x throughput improvement on average than lock-based FPGA implementations and optimized CDS algorithms on a state-of-the-art multi-core CPU respectively.
Keywords: pc2-harp-ressources

Automatic Offloading of Cluster Accelerators - Ceissler, Ciro; Nepomuceno, Ramon; Pereira, Marcio; Araujo, Guido (2018 IEEE 26th Annual International Symposium on Field-Programmable Custom Computing Machines (FCCM))
The sheer amount of computing resources required to run modern cloud workloads has put a lot of pressure on the design of power efficient cluster nodes. To address this problem, Intel (HARP) and Microsoft (Catapult) have proposed CPU-FPGA integrated architectures that can deliver efficient power-performance executions. Unfortunately, the integration of FPGA acceleration modules to software is a challenging endeavor that does not have a seamless programming model. This paper proposes HardCloud (www.hardcloud.org), an extension of the OpenMP 4.X standard that eases the task of offloading FPGA modules to cluster accelerators.
Keywords: pc2-harp-ressources

A Case Study in Using OpenCL on FPGAs: Creating an Open-Source Accelerator of the AutoDock Molecular Docking Software - Solis-Vasquez, Leonardo; Koch, Andreas (FSP Workshop 2018; Fifth International Workshop on FPGAs for Software Programmers)
In recent years, OpenCL has been increasingly adopted as it enables software programmers to harness the performance and power efficiency of FPGAs. Despite simplifying the FPGA programming challenge, achieving high performance and energy efficiency with OpenCL is still a difficult task. In order to further contribute to the advance of the OpenCL usage for FPGAs, we utilize a realistic application scenario as our case study: the AutoDock molecular docking software. While OpenCL has proven its effectiveness in accelerating molecular docking on GPUs, for FPGA-based AutoDock accelerators it struggles with difficult design patterns. Besides complex multiple-producers to single-consumer datapaths, these include time-intensive loops with variable runtimes. Therefore, this work presents the design and optimization steps for implementing AutoDock in OpenCL targeting an Arria-10 FPGA, as well as a corresponding execution runtime and energy-efficiency evaluation. Applying these techniques improved the performance of the initial OpenCL implementation for FPGAs by three orders of magnitude, with the final version of the code now yielding speed-ups of up to ~2.7x, and energy-efficiency gains of up to ~1.8x over the original serial AutoDock version executing on a current-generation CPU.
Keywords: pc2-harp-ressources

Competitive Evaluation of Energy Management Strategies for Hybrid Electric Vehicle Based on Real World Driving - Kemper, Philipp; Rehlaender, Philipp; Witkowski, Ulf; Schwung, Andreas (2017 European Modelling Symposium (EMS))

A fuel cell vehicle thermal system model - Rehlaender, Philipp; Kemper, Philipp; Schwung, Andreas; Witkowski, Ulf (2018 IEEE International Energy Conference (ENERGYCON))

A Novel Predictive Energy Management System - Rehlaender, Philipp; Kemper, Philipp; Schwung, Andreas; Witkowski, Ulf (2017 European Modelling Symposium (EMS))

Control of a fuel cell vehicle thermal management system - Rehlaender, Philipp; Kemper, Philipp; Schwung, Andreas; Witkowski, Ulf (2018 IEEE International Energy Conference (ENERGYCON))

Improved Neural Control of Movements Manifests in Expertise-Related Differences in Force Output and Brain Network Dynamics - Gölz, Christian; Voelcker-Rehage, Claudia; Mora, Karin; Reuter, Eva-Maria; Godde, Ben; Dellnitz, Michael; Reinsberger, Claus; Vieluf, Solveig (Frontiers in Physiology)

Age- and Expertise-Related Differences of Sensorimotor Network Dynamics during Force Control - Vieluf, Solveig; Mora, Karin; Gölz, Christian; Reuter, Eva-Maria; Godde, Ben; Dellnitz, Michael; Reinsberger, Claus; Voelcker-Rehage, Claudia (Neuroscience)

Transition Manifolds of Complex Metastable Systems - Bittracher, Andreas; Koltai, Péter; Klus, Stefan; Banisch, Ralf; Dellnitz, Michael; Schütte, Christof (Journal of Nonlinear Science)

Die „neue“ MaRisk (BA) 9/2017 - Krimphove, Dieter (Zeitschrift für Bank- und Kapitalmarktrecht BKR)

Do we betray errors beforehand? The use of eye tracking, automated face recognition and computer algorithms to analyse learning from errors. - Harteis, Christian; Fischer, Christoph; Töniges, Torben; Wrede, Britta (Frontline Learning Research)

The journey to proficiency: Exploring new objective methodologies to capture the process of learning and professional development. - Harteis, Christian; Kok, Elen; Jarodzka, Halszka (Frontline Learning Research)

2018 IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC) - Cunha, Jácome; Fernandes, Joao Paulo; Kelleher, Caitlin; Mendes, Jorge; Engels, Gregor (Proceedings of 2018 IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC), Lisbon, Portugal, October 1-4, 2018)

Gerechtigkeit in flexiblen Arbeits- und Managementprozessen - Engels, Gregor; Maier, Günter W.; Ötting, Sonja K.; Steffen, Eckhard; Teetz, Alexander (Zukunft der Arbeit – Eine praxisnahe Betrachtung)

Die effektive Konjugationslänge ist für die spektrale Verschiebung im rot/grün schaltenden Cyanobakteriochrom Slr1393g3 verantwortlich - Wiebeler, Christian; Rao, Aditya G.; Gärtner, Wolfgang; Schapiro, Igor (Angewandte Chemie)
Keywords: pc2-ressources